AI-Mediated Communication in E-Commerce: Implications for Customer Trust - Christine Hennighausen; Vanessa Gabriela Yarza Navarro-Schär; Eric Eller (International Journal of Consumer Studies, 2025)
Generative artificial intelligence (AI) technologies offer new potential for marketing and customer operations, such as automation and personalization of customer service. However, more must be understood about how AI-mediated communication (AI-MC) affects customer trust. We conducted an online experiment to investigate the impact of AI-MC on customer trust in an online retail context. We presented N 0.167em=0.167em294 participants with two email scenarios describing a product return context, labeled as written by either (a) a service employee, (b) a service employee assisted by AI, or (c) AI on behalf of the service employee. We further varied levels of service criticality to consider customers' perception of vulnerability. Our findings revealed higher customer trust ratings in the online retailer when the email communications were written by the service employee, compared to those written by the service employee assisted by AI. When analyzing the different components of trust, it was found that communications written by the service employee assisted by AI reduced perceptions of both the online retailer's benevolence and integrity, while communications written by AI on behalf of the employee led to lower perceived integrity of the online retailer. Surprisingly, service criticality did not affect trust ratings. We discuss the managerial implications of integrating generative AI into customer service in the context of the EU AI Act, which came into force on 1 August 2024.
Keywords: 330; AI-mediated communication (AI-MC); artificial intelligence; CRM; customer trust; E-commerce; generative AI; service criticality